Identification of a Fusobacterial RNA-binding protein involved in host small RNA-mediated growth inhibition - Pu-Ting Dong; Mengdi Yang; Jie Hu; Lujia Cen; Peng Zhou; Difei Xu; Peng Xiong; Jiahe Li; Xuesong He (International Journal of Oral Science)
Abstract Host-derived small RNAs are emerging as critical regulators in the dynamic interactions between host tissues and the microbiome, with implications for microbial pathogenesis and host defense. Among these, transfer RNA-derived small RNAs (tsRNAs) have garnered attention for their roles in modulating microbial behavior. However, the bacterial factors mediating tsRNA interaction and functionality remain poorly understood. In this study, using RNA affinity pull-down assay in combination with mass spectrometry, we identified a putative membrane-bound protein, annotated as P-type ATPase transporter (PtaT) in Fusobacterium nucleatum (Fn), which binds Fn-targeting tsRNAs in a sequence-specific manner. Through targeted mutagenesis and phenotypic characterization, we showed that in both the Fn type strain and a clinical tumor isolate, deletion of ptaT led to reduced tsRNA intake and enhanced resistance to tsRNA-induced growth inhibition. Global RNA sequencing and label-free Raman spectroscopy revealed the phenotypic differences between Fn wild type and PtaT-deficient mutant, highlighting the functional significance of PtaT in purine and pyrimidine metabolism. Furthermore, AlphaFold 3 prediction provides evidence supporting the specific binding between PtaT and Fn-targeting tsRNA. By uncovering the first RNA-binding protein in Fn implicated in growth modulation through interactions with host-derived small RNAs (sRNAs), our study offers new insights into sRNA-mediated host-pathogen interplay within the context of microbiome-host interactions.